Upaya Meningkatkan Pemahaman Konsep Peserta Didik pada Muatan IPA Ekosistem Kelas V Sekolah Dasar Menggunakan Video Interaktif - Sri Wahyuni; Ahmad Hariandi; Alirmansyah Alirmansyah (Departement of Mathematics Education, 2023)
This study aims to find out the efforts to improve students' conceptual understanding of the science content of ecosystems for class V elementary schools using interactive videos at SD N 10/IV Jambi and to find out the process of applying interactive video content to the science ecosystem content for class V elementary schools at SD N 10/IV Jambi. This research was conducted at SD N 10/IV Jambi. The research data were obtained by means of interviews with science students and teachers at SD N 10/IV Jambi and school documentation. After the data is collected, the data is analyzed descriptively. Based on the results of the researchers and data analysis, it can be concluded that interactive videos can improve students' understanding of the concept of ecosystem science content for class V SD N 10/IV Jambi. This can be seen from the results of student test assessments in the first cycle of student learning average of 60.28% at the first meeting with 2 students' mastery or 11.11% and at the second cycle I meeting the second student learning average was 66.56 % with completeness of 5 students or 27.78%. In cycle II, the average understanding of students' concepts reached 72.94% at the first meeting with 14 students' completeness or 77.78% and in cycle II, the second meeting, the average student learning was 83.94% with 18 students' completeness or 100%. This shows that students' understanding of concepts increases in learning in each cycle. Increased students' understanding of concepts from cycle I to cycle II of 72.22% with high.